Interaction Analysis of Collinear Two Cracks with Unequal Length under Uniaxial Traction. (22nd May 2019) - Yu, Bin; Xi, Jingyi; Chen, Zhonghui; Zhang, Lingfan
Abstract : The interaction among different sizes of cracks in materials is one of the key factors leading to the damage of brittle materials. Based on the Kachanov method, the expressions for the stress intensity factors of two collinear cracks with unequal length were obtained and the interaction effect was analyzed. A compression test of a cement mortar specimen containing two cracks and numerical analysis usingR F P A 2 D were performed. The results indicate that the crack interaction can almost be neglected when the crack distance reaches the length of the large crack; the two respective collinear cracks in the specimen grow and do not affect each other when the crack distance reaches the large crack length. The results of compression test and numerical analysis are both in agreement with the theoretical result.